1979
DOI: 10.1007/bf01317900
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on a vaccinia virus cytotoxin present in infected cell extracts: Identification as surface tubule monomer and possible mode of action

Abstract: A vaccinia virus-specific cytotoxic protein (3--10 X 10(4) daltons) had previously been detected in extracts of infected HeLa cells. In this study the protein has been shown to be a late gene product and a virion component--almost certainly the monomer of the surface tubules of the vaccinia virion. The relationship of this cytotoxin to a number of early vaccinia-induced cytopathic effects was examined: it was not the mediator of vaccinia-induced early cell rounding, did not inhibit protein or RNA synthesis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although vaccinia surface tubule (s.t.) protein isolated from virions or infected cells was cytotoxic when introduced into cells by hypertonic shock, it did not rapidly inhibit protein synthesis by intact HeLa cells or cell-free extracts (Wolstenholme et al 1977;Burgoyne & Stephen 1979). These results indicated that this viral cytotoxin acts from within, possibly causing the degeneration of cells that occurs at late times after vaccinia infection, rather than from without at the time of the early shut-off phenomenon.…”
Section: A J Shatkin V Accinia a Highly Cytocidal Dna Virusmentioning
confidence: 89%
“…Although vaccinia surface tubule (s.t.) protein isolated from virions or infected cells was cytotoxic when introduced into cells by hypertonic shock, it did not rapidly inhibit protein synthesis by intact HeLa cells or cell-free extracts (Wolstenholme et al 1977;Burgoyne & Stephen 1979). These results indicated that this viral cytotoxin acts from within, possibly causing the degeneration of cells that occurs at late times after vaccinia infection, rather than from without at the time of the early shut-off phenomenon.…”
Section: A J Shatkin V Accinia a Highly Cytocidal Dna Virusmentioning
confidence: 89%
“…Several mechanisms are responsible for this effect on cells. 3,4,11,20,25,33,41,61,88,95,105,114,121,122,125,138 In some instances, cell metabolism is drastically altered. Macromolecular synthesis may be inhibited by a variety of mechanisms and may occur at the level of replication, transcription, or translation.…”
Section: Lytic Viral Infectionsmentioning
confidence: 99%